2019
DOI: 10.1093/infdis/jiz517
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Host-Directed Therapy With Statins Improves Tuberculosis-Related Outcomes in Mice

Abstract: Background Tuberculosis (TB) treatment is lengthy and complicated and patients often develop chronic lung disease. Recent attention has focused on host-directed therapies aimed at optimizing immune responses to Mycobacterium tuberculosis (Mtb), as adjunctive treatment given with antitubercular drugs. In addition to their cholesterol-lowering properties, 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (statins) have broad anti-inflammatory and immunomodulatory activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 47 publications
1
66
0
Order By: Relevance
“…Among all statins, pravastatin exhibited the most potent adjunctive activity with the least toxicity by modulating phagosomal maturation characteristics in THP-1 macrophages. These observations concluded that pravastatin can be an attractive candidate for host-directed, adjunctive TB therapy [13]. All in vitro studies are summarized in Table 1.…”
Section: What Do Studies Suggest Regarding Anti-tb Effects Of Statin mentioning
confidence: 94%
See 3 more Smart Citations
“…Among all statins, pravastatin exhibited the most potent adjunctive activity with the least toxicity by modulating phagosomal maturation characteristics in THP-1 macrophages. These observations concluded that pravastatin can be an attractive candidate for host-directed, adjunctive TB therapy [13]. All in vitro studies are summarized in Table 1.…”
Section: What Do Studies Suggest Regarding Anti-tb Effects Of Statin mentioning
confidence: 94%
“…To determine whether statins can enhance the activity of anti-TB drugs against intracellular bacilli in macrophages, Dutta et al conducted another study in 2019 [13]. They performed experiments with the M. TB H37Rv and THP-1 macrophages infected at MOI of 20.…”
Section: What Do Studies Suggest Regarding Anti-tb Effects Of Statin mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, their use has been explored against multisystem microbial infections, such as sepsis and pneumonia, and in non-infectious pathologies, such as autoimmune and inflammatory diseases (18-20). In regard to tuberculosis, statins exhibit anti-tubercular activity in murine and human macrophages infected ex vivo (9, 12, 13), display immunomodulatory effects in ex vivo infected human peripheral blood cells (13), and shorten the duration of antibiotic treatment in M. tuberculosis -infected mice (10, 11). Previous work (9) found a reduction in M. tuberculosis burden in murine macrophages by high doses of statins that inhibited both the cholesterol- and isoprenoid-forming branches of the mevalonate pathway.…”
Section: Introductionmentioning
confidence: 99%